Determinants of Private Brand Purchase in the Central Klang Valley Area - Oh, Yoke Moi (2000)
Private brands play a critical role in retail strategy. This concept will help retailers to outshine other retailers as well as compete effectively with manufacturers. Yet, we hardly find research being conducted on Malaysians interests in buying private brands. However, we have come across a number of studies concerning private brand proneness in other countries. Lately many research regarding the relationship between private brand proneness and behavioural aspects of consumers were carried out. The most recent research on this subject is conducted by Richardson et al., (1996a). This current research is done replicating their conceptual framework. Our study augments prior research by building an integrated framework within which to view private brand proneness in the context of Malaysia, namely in the Central Klang Valley area. This study was conducted by using non-probability sampling method. Reliability test was used to purify the data and to ensure internal reliability of the data from 200 respondents before factor analysis is used to reduce the data. The correlation among factors was tested by using Pearson correlation analysis. From the findings we found that most of the consumers (78.6%) in the Central Klang Valley area have bought private brands before but out of these only 11 % can be considered as "frequent" private brand buyers. One positive sign here is that we have about 46.7% consumers who have claimed to buy private brands once in a while (sometimes). This group of consumers can be considered as "potential private brand buyers". Retailers can focus on this group of people as a new segment. These consumers need to be fed with more information about private brands in order to remove their doubts on private brands. We also found that most of the private brand consumers are aged between 31-40 and in the range of monthly household income ofRM3,OOOto RM7,000. Perceptual factors are found to be influencing private brand proneness. These factors include, familiarity with private brands, the extent to which consumers rely on external cues, perceived quality variation between national and private brands, perceived risk, perceived value for money, brand consciousness and finally the extent of consumer's intention in purchasing a private brand. GeneraJly speaking, most of the consumers in the Central Klang Valley area are still doubtful about private brands due to the limited information given to them in their decision-making process. Marketers should create market awareness and provide more information about private brands through the implementation of various promotional activities. Marketing implications for retail strategies pertaining to private brand management are also discussed